Russian consumer lending market in modern conditions - I. A. Rizvanova (Вестник университета)
In the current conditions, the Russian financial market has demonstrated its stability and ability to promptly respond to the ongoing changes in the geopolitical sphere, while the banks that control more than 80 % of the country’s assets are under sanctions. The article considers and analyzes the Russian consumer lending market in modern conditions. It reviews the crisis periods of the Russian financial market from 2014 to 2023 and the anti-crisis measures of the Central Bank of the Russian Federation, the domestic consumer credit market in the current realities, and loans restructuring to individuals under sanctions pressure. The purpose of the study is to determine main trends in the consumer credit market development based on the analysis of the Russian consumer credit market under sanctions pressure. The object of the study is the domestic consumer credit market in modern conditions. The subject of the study is trends in the Russian consumer credit market development under sanctions pressure. The sources of information were analytical materials and statistical reporting data of the Central Bank of the Russian Federation, laws and regulations, domestic and foreign scientific literature, and analytical and reference online resources.